Desensitization with antigen-specific immunoadsorption interferes with complement in ABO-incompatible kidney transplantation - Biglarnia, Ali-Reza ; 0009-0004-2293-0740; Nilsson, Bo; Nilsson Ekdahl, Kristina; Tufveson, Gunnar; Nilsson, Thomas; Larsson, Erik; Wadström, Jonas (Transplantation, 2012)
BACKGROUND: Complement activation was characterized during and after desensitization treatment in 19 consecutive patients receiving ABO-incompatible (ABOi) living donor kidney transplants to assess the effect of desensitization protocol including antigen-specific immunoadsorption (IA) on complement activation. METHODS: All patients received rituximab- and tacrolimus-based triple treatment. Anti-A/B antibodies were removed by IA. Serial determinations of C3, C3a, the C3a/C3 ratio, and sC5b-9 were carried out between day -30 and postoperative day 30. C1q was measured on day -30 and the day before the transplantation. In two recipients, eluates from immunoadsorbent columns were analyzed for C3a, C1q, and immunoglobulins by western blotting. Same complement analysis was performed in eluate from a control column after in vitro perfusion of AB-plasma. RESULTS: Patient and graft survival were 100% for a median follow-up of 40 months (range, 12-60 months). There were no humoral rejections based on ABO-antigen-antibody interactions. C3a and the C3a/C3 ratio declined with the start of IA treatment, and this decline was maintained postoperatively. C1q declined from day -30 to a lower value on the day before transplantation (P<0.05). In eluates from both patient and control, immunoadsorbent column immunoglobulins together with C3a and C1q were detected. CONCLUSIONS: The current protocol including antigen-specific IA interferes with the complement system; this effect may be partially responsible for the absence of humoral rejection resulting from ABO-antigen-antibody interactions and the excellent outcomes obtained after ABO-incompatible kidney transplantation.
Keywords: ABO Blood-Group System/immunology; Adult; Aged; Antibodies/blood; Blood Group Incompatibility/immunology; Cohort Studies; Complement Activation/physiology; Complement C1q/metabolism; Complement C3/metabolism; Complement C3a/metabolism; Desensitization, Immunologic/methods; Female; Follow-Up Studies; Graft Rejection/epidemiology; Graft Survival/immunology; Humans; Immunity, Humoral/physiology; Immunosorbents/immunology; Incidence; Kidney Transplantation/immunology; Living Donors; Male; Middle Aged; Retrospective Studies